اتجاهات الشباب الجامعي نحو كبار السن - الجبوري، عباس رمضان (الأكاديمية الأمريكية العربية للعلوم والتكنولوجيا, 2010)
هدفت هذه الدراسة إلى تعرف الفروق في الاتجاهات بين (الذكور- الإناث)، والتخصص (علمي- أدبي)، والمرحلة الدراسية (أولى- ثانية- ثالثة- رابعة)، والفروق في الاتجاهات بين الطلبة الذين يوجد في أسرهم مسن وبين الطلبة الذين لا يوجد في أسرهم مسن. أعد الباحث مقياس للاتجاه نحو المسنين مكون من (45) فقرة وتتوافر مؤشرات الصدق والثبات، تم تطبيق المقياس على عينة من (160) طالبا وطالبة، وأشارت نتائج اختبار "ت" وتحليل التباين الثلاثي إلى أن متغير التخصص دال لصالح التخصص العلمي، والتفاعل بين التخصص والجنس دال لصالح فئة الإناث علمي، وباقي المتغيرات غير دالة إحصائيا. وبناء على ذلك خلصت الدراسة إلى مجموعة من الاستنتاجات، والتوصيات. The aim of this study is to explore differences in attitudes of university students towards elderly people according to sex, specialization and academic level. The study also attempts to find out whether there is a differences in attitudes whether the students have elderly people in their family or not. An attitude scale, contained 45 items was applied to 160 male and female students. The scale has good indices of validity and reliability. Using T. test and three-way ANOVA, the results showed significant differences according to specialization in favor of science specialization. The interaction between sex and specialization was also significant, in favor of science female students. No other variables were significant. Finally, several conclusions and suggestions for further research were presented.
Keywords: طلاب الجامعات -- العراق -- التعليم الجامعي -- الجامعة المستنصرية -- اتجاهات طلاب الجامعات -- المسنون -- الجوانب الاجتماعية -- الجوانب الصحية -- الشيخوخة